Volatilitas Suara Partai Politik Dalam Pemilihan Umum Dewan Perwakilan Rakyat Daerah (DPRD) Kabupaten Semarang Tahun 2014-2024 - Arinta Mustika Baiti Baiti; Zudi Setiawan Setiawan (Universitas Wahid Hasyim Semarang, 2026)
This study aims to determine the volatility of political parties and the causes of the volatility of political party votes in the 2014-2024 Semarang Regency DPRD general election. The type of research used is qualitative research combined with qualitative in numeric with a descriptive approach. The results of this study show that the Semarang Regency DPRD election volatility index is low, with an average of 26.29 in the last three elections. This can be seen in the 2019 Election Volatility Index of 33.05 decreasing to 19.54 in the 2024 Election. Low volatility indicates a strong relationship between parties and constituents that leads to stable election results while also indicating openness or rationality of voters. Low volatility is caused by two factors, namely (1) internal party factors (party organization) which refer to loyalty, social roots, division or cohesion and party electoral performance (2) external factors (volatility of the party system) which refer to the election system, political party format, ideological polarization and media coverage. Keywords: Elections, Political Parties, Volatility